INTERPRETATION OF THE VERSES ABOUT ISLAMIC EDUCATION FACILITIES AND INFRASTRUCTURE - Rahmat Hidayat; Zulaika Zulaika; Rica Widiastuti; Wahida Rayhan Nasution (Universitas Dharmawangsa, 2021)
Management of facilities and infrastructure is the process of cooperating efforts in managing the existing facilities and infrastructure in educational institutions, functioned according to their needs and utilization. This type of research is library research (library research) and is included in the category of qualitative research with thematic methods (maudu'iy. Furthermore, the technical analysis of the data in this study uses the content analysis method. Content analysis is a research technique to make conclusions. conclusions (inference) that can be imitated (replicable) and with valid data, by paying attention to the context The results of this study indicate that the facilities and infrastructure in the context of Islamic education cannot be separated from the Qur'an and hadith, including: QS. ]: 68-69 which explains that the learning contained in bees is one of the reasons for the importance of the facilities and infrastructure of Islamic education. In addition, QS. Al - An'am [6]: 153 uses lines as an educational tool to explain what is he wanted to convey to his friends Al-Ghasiyah [88]: 17-21 The verse describes nature as a means of a means to magnify the greatness of Allah SWT which covers the heavens and the earth. QS. Al-Maidah [5]: 31 explains that in carrying out the learning process must use relevant learning media. QS. AlMujadalah [58]: 11 The verse explains how we manage facilities and infrastructure, not only the utilization that must be considered, the implementation method must also have rules, how to seat rules, how to behave when seeing one of his friends is in trouble and not. get a seat, how to respond when someone provides space in a knowledge assembly, this if applied, in addition to gaining rewards and degrees, it will also be able to create a peaceful and comfortable learning atmosphere making it easier for educators to convey knowledge and students easily acquire knowledge and in the end it is also easy to process the expected learning objectives